PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR SISWA PADA MATA PELAJARAN PKn DI KELAS V SD SWASTA KATOLIK BUDI MURNI II MEDAN TAHUN AJARAN 2025/2026 - Darinda Sofia Tanjung; Hulu, Fransiska Carlin Mega Putri; Juni Lestari Telaumbanua; Yolan Dita Marbun; Surado Mansari Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' learning discipline through the application of the Student Teams Achievement Division (STAD) cooperative learning model in Civics (PKn) subjects in grade V-5 of Budi Murni II Medan Catholic Private Elementary School in the 2025/2026 Academic Year. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles. Each cycle includes the planning, action implementation, observation, and reflection stages. The research subjects were 32 students. Data collection techniques were carried out through observations of student learning discipline and learning outcome tests. Data were analyzed using quantitative descriptive analysis by calculating the percentage of achievement of discipline indicators and completeness of learning outcomes. The results showed that the application of the STAD cooperative learning model was able to significantly improve students' learning discipline. The average percentage of learning discipline increased from 55.00% in Cycle I to 93.75% in Cycle II. The improvement in discipline was followed by an improvement in student learning outcomes, as indicated by an increase in the average class score from 71.72 to 96.41, while the percentage of learning completion increased from 56.25% to 100%. The research findings indicate that the STAD cooperative learning model is able to create more active, collaborative, and responsible learning, making it effective in improving learning discipline as well as student learning outcomes in Civics subjects in elementary schools.